Design and fabrication of agriculture wheel pump / Muhammad Hakimi Hamsah - Hamsah, Muhammad Hakimi (2023)
The main purpose of producing this product is to enable farmers and gardeners to make the process of spraying waters, pesticides and herbicides to their gardens becomes more effective. It helps the farmers and gardeners work because they no longer need to carry the tank on their back that can cause their back strain and hurt. This product only has to be push to forward just like how the trolley function and then it will generate mechanically pump by the set of power transmission part by using shaft, bearings and set of sprockets. Energy to pump the tank pump can be reduced. Next, it also comes with a some of nozzles on the wing. With nozzles on the wing, it can speed up the spraying process as it can spray left and right side at the same time. In conclusion, this product can help farmers gardeners in terms of comfort during spraying, reducing energy to pump tanks, and effectively utilizing spraying time. The expected result for this project is, with this project the farmer will take lees time and energy in spraying process.